2007
DOI: 10.2754/avb200776010121
|View full text |Cite
|
Sign up to set email alerts
|

Egg Yolk Colour Depending upon the Composition of the Feeding Mixture for Laying Hens

Abstract: The aim of this study was to verify the possibility of replacement of fish meal by specially treated meal made of yellow lupin seed in relation to the yolk colour. The experiment was performed with 72 laying hens divided into two groups. The experimental group including 36 laying hens received a feeding mixture containing meal made of yellow lupin seed (the JUNO variety) which replaced fish meal used as an animal protein component in feeding mixtures in the control group. Samples of eggs were collected monthly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…Not only higher values of egg content pH and of HU units were determined, but also there was a decrease in the thickness, strength and share of egg shell in the egg weight. Dvořák et al (2007) observed improved egg quality parameters after adding lupin to hen feed. Watkins and Mirosh (1987) confirmed the lack of significant differences in the HU units of eggs among treatments of hens fed diets containing 10, 15, 20, 25 and 30% white lupin seeds, but 30% share of this feed component in the diet led to a decrease in egg production.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Not only higher values of egg content pH and of HU units were determined, but also there was a decrease in the thickness, strength and share of egg shell in the egg weight. Dvořák et al (2007) observed improved egg quality parameters after adding lupin to hen feed. Watkins and Mirosh (1987) confirmed the lack of significant differences in the HU units of eggs among treatments of hens fed diets containing 10, 15, 20, 25 and 30% white lupin seeds, but 30% share of this feed component in the diet led to a decrease in egg production.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, in our study, the presence of yellow lupin seeds in laying hen diets improved some egg quality parameters. Sikder et al (1998) and Dvořák et al (2007), and also many other authors, have underlined the fact that dietary composition significantly influences yolk colour -an important egg quality index for consumers. In our experiment, significant improvement of yolk colour (La Roche scale) was obtained as an effect of the rise in yellow lupin seeds content in the diets and increased levels from 1.59 (in group with 10% yellow lupin seeds addition) to 3.97 (in group with 25% yellow lupin seeds addition) in 1 kg of feed mixture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All egg yolk measurements were done automatically three times. The resulting value was the average of the three measured values 8, 9. The results for parameters L *, a *, b * were divided into categories.…”
Section: Methodsmentioning
confidence: 99%
“…The feed mixtures only consisted of plant-based components. Meal made from the yellow lupine variety JUNO seeds, which is also an important source of plant pigments (Dvořák et al 2007), was one of the components. No artificial colourings were used, natural pigments originated from feed components.…”
Section: Methodsmentioning
confidence: 99%